Cognitive Biases and Behavioral Patterns Shaping Investment Decision-Making: Kecenderungan Kognitif dan Pola Perilaku yang Mempengaruhi Pengambilan Keputusan Investasi - Fadi Hassan Jaber (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Traditional financial theories, such as the Efficient Market Hypothesis and Modern Portfolio Theory, assume rational, utility-maximizing investors. Specific Background: However, empirical evidence shows persistent cognitive and emotional biases—loss aversion, overconfidence, herding, mental accounting, and anchoring—that distort investment decisions and market outcomes. Knowledge Gap: Despite growing interest in behavioral finance, there remains insufficient synthesis that integrates these psychological factors with conventional financial frameworks, particularly across diverse contexts. Aims: This study conducts a comprehensive literature review to examine how behavioral finance theories influence individual and institutional investment decisions. Results: The findings reveal that systematic biases shape investor behavior by driving excessive risk-taking, irrational asset allocation, and susceptibility to market inefficiencies, thereby challenging rational-choice models. Novelty: Unlike prior works, this review offers a structured thematic synthesis of behavioral concepts, highlights empirical patterns across global studies, and underscores the interdisciplinary relevance of psychology in finance. Implications: The study calls for reform in financial education, the integration of behavioral diagnostics into fintech, and the development of policy tools informed by cognitive biases, ultimately contributing to more resilient investment strategies and adaptive financial systems.Highlights: Investor decisions are often shaped by psychological biases rather than rational models. Behavioral finance provides tools to anticipate and correct irrational market behaviors. Integrating psychology into financial education and policy enhances decision-making. Keywords: Behavioral Finance, Investment Decisions, Cognitive Biases, Prospect Theory, Market Inefficiency